2018
DOI: 10.1002/ana.25218
|View full text |Cite
|
Sign up to set email alerts
|

Developmental conduction aphasia after neonatal stroke

Abstract: Objective: Impairment of speech repetition following injury to the dorsal language stream is a feature of conduction aphasia, a well-described "disconnection syndrome" in adults. The impact of similar lesions sustained in infancy has not been established. Methods: We compared language outcomes in term-born individuals with confirmed neonatal stroke (n 5 30, age 5 7-18 years, left-sided lesions in 21 cases) to matched controls (n 5 40). Injury to the dorsal and/or ventral language streams was assessed using T 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 62 publications
(163 reference statements)
0
28
0
Order By: Relevance
“…These results confirmed that language expression is associated with multiple brain areas [12]. To date, literature studies investigated the neural reorganizations in patients with conduction aphasia in terms of diagnosis and neuroimaging evidence [13][14][15][16]. Few studies provided evidence in terms of brain plasticity after an intensive rehabilitative process in patients with conduction aphasia, in fact it was demonstrated that early aphasia rehabilitation is associated with a more recruitment of brain areas, particularly the left inferior frontal gyrus [17].…”
Section: Introductionmentioning
confidence: 62%
“…These results confirmed that language expression is associated with multiple brain areas [12]. To date, literature studies investigated the neural reorganizations in patients with conduction aphasia in terms of diagnosis and neuroimaging evidence [13][14][15][16]. Few studies provided evidence in terms of brain plasticity after an intensive rehabilitative process in patients with conduction aphasia, in fact it was demonstrated that early aphasia rehabilitation is associated with a more recruitment of brain areas, particularly the left inferior frontal gyrus [17].…”
Section: Introductionmentioning
confidence: 62%
“…Early theories of the ontogeny underpinning brain organization have swayed between the extremes of early specialization (8,9) and equipotentiality/age-dependent plasticity (10), with both positions surviving the test of time with help from the application of neuroimaging techniques (e.g., refs. [11][12][13]. Recognizing the undeniable fact that in the absence of early brain damage the vast majority of adult individuals exhibit hemispheric specialization, most notably for speech and language, and cognizant of the need for compatibility between neuronal plasticity and early hemispheric equipotentiality, a number of researchers have argued for a middle ground between the 2 extremes 14, with the view that "constrained plasticity" (15), or "ontogenetic specialization" (16) progressively unfolds during brain maturation.…”
Section: Age At Injury Equipotentiality and Specializationmentioning
confidence: 99%
“…For instance, studies of children with brain injury have shown that early damage to the AF may be succesfully compensated through recruitment of ipsilateral and contralateral brain areas and tracts, resulting in an average performance on multiple language tasks (Rauschecker et al, 2009;Asaridou et al, 2020), although some deficits may persist (Yeatman and Feldman, 2013). In this line, after early brain damage, functional and structural rightward lateralization of the dorsal pathway is associated with better language outcomes (Northam et al, 2018;Francois et al, 2019). Despite this evidence, spontaneous readjustment of the language system after brain lesion seems to be limited as evidenced by the frequent persistence of language deficits (Tavano et al, 2009;Turkstra et al, 2015;Francois et al, 2016).…”
Section: Introductionmentioning
confidence: 99%